Churches and social power in early medieval Europe: integrating archaeological and historical approaches - Sánchez Pardo, José Carlos; Shapland, Michael G. (Studies in the early Middle Ages, 2015)
A comparative and interdisciplinary approach to secular power and the foundation of medieval churches. 0Local churches were an established part of many towns and villages across early medieval Western Europe, and their continued presence make them an invaluable marker for comparing different societies. Up to now, however, the dynamics of power behind church building and the importance of their presence within the landscape have largely been neglected.00This book takes a comparative and interdisciplinary approach to the study of early medieval churches, drawing together archaeology, history, architecture, and landscape studies in order to explore the relationship between church foundation, social power, and political organization across Europe. Key subjects addressed here include the role played by local elites and the importance of the church in buttressing authority, as well as the connections between archaeology and ideology, and the importance of individual church buildings in their broader landscape contexts.00Bringing together case-studies from diverse regions across Western Europe (Italy, Spain, Portugal, Germany, France, the British Isles, Denmark, and Iceland), the seventeen contributions to this volume offer new insights into the relationships between church foundations, social power, and political organization. In doing so, they provide a means to better understand social power in the landscape of early medieval Europe